If you Were a Homonym or a Homophone - Loewen, Nancy; Illustrated by Gray, Sara (Minneapolis Picture Window Books, 2007)
Learn what a homonym or homophone is in a fun and easy way.
Include colour illustrations
Keywords: English language--Homonyms